Influence of thermomechanical aging on microstructure and mechanical properties of 2519A aluminum alloy - Wang, Hui-min; Xia, Chang-qing; Lei, Pan; Wang, Zhi-wei (Journal of Central South University, 2011)
The influence of thermomechanical aging on microstructure and mechanical properties of 2519A aluminum alloy was investigated by means of microhardness test, tensile test, optical microscopy (OM) and transmission electron microscopy (TEM). The results show that 50% cold rolling deformation prior to aging is beneficial since it promotes a more homogeneous distribution of the precipitation phase and reduces the number of precipitation phase on the grain boundaries, and thus shrinks the total volume of precipitation-free zones at grain and sub-grain boundaries. As a result, the tensile properties of 2519A aluminum alloy have been significantly improved.